Pertumbuhan Rumput Gajah Kerdil (Pennisetum purpureum ‘Mott’) di Lahan Terbuka Bekas Penambangan Batu Kapur Kawasan Karst Gombong Jawa Tengah - Doso Sarwanto; Sari Eko Tuswati (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
The negative impact of limestone mining on a karst area around Gombong is the destruction of ecosystem. Ecosystem’s destruction will decrease the variety, productivity, quality and continuity of indigenous livestock forages. The aim of this research is to know the growth rate of Dwarf Elephant grass (Pennisetum purpureum 'Mott') in the post mining limestone with various methods of planting. The method used in this research is an experimental method in an open field that was used for limestone mining by using Completed Random Design. The treatment consists of 4 kinds of planting methods with 4 repetitions, while the research treatment used in this experiment is the RG (the field with Dwarf Elephant Grass); RGL (the field with Dwarf Elephant Grass + peanut legume); RGK (the field with Dwarf Elephant Grass + goat’s compost 1,5 kg/m2) and RGKL (the field with Dwarf Elephant Grass + peanut legume + goat’s compost 1,5 kg/m2). The parameter used for the research is the growth rate which includes the plant’s height, the length of the leaves, and also the width of Dwarf Elephant Grass’s leaves (Pennisetum purpureum ‘Mott’) until the 8th week.The result of this research shows that the use of goat’s compost 1,5 kg/m2 and planting of peanut can give significant results to the growth of Dwarf Elephant Grass in open field that was used for limestone mining.